Analysis of Different Load Balancing Techniques (International Journal of Communication Systems and Network Technologies, 2024)
Cloud computing is a popular paradigm which provides on-demand services to the user. As needs of the user changes dynamically, it is the responsibility of the cloud service provider to handle the requests efficiently and to satisfy the demands of end user by ensuring quality of service. Cloud computing suffers from umpteen critical problems which needs to be explored. One such problem is Load Balancing. It distributes the load evenly among the nodes with a condition that no overloading of the node occurs. So, it is better to schedule the tasks in an intelligent manner to utilize the resources efficiently. Task Scheduling is an important research area in cloud computing. It deals with the NP-hard problems. To find the near optimal solution, meta-heuristic techniques are used. In this paper, an  in-depth review of different task scheduling algorithms based on load balancing have been discussed. We have compared these algorithms on the basis of pros and cons.
Keywords: Cloud Computing; Load Balancing Algorithms; Task Scheduling